2018
DOI: 10.1038/s41598-017-17353-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing kinetic fractionation in brachiopod calcite using clumped isotopes

Abstract: Brachiopod shells are the most widely used geological archive for the reconstruction of the temperature and the oxygen isotope composition of Phanerozoic seawater. However, it is not conclusive whether brachiopods precipitate their shells in thermodynamic equilibrium. In this study, we investigated the potential impact of kinetic controls on the isotope composition of modern brachiopods by measuring the oxygen and clumped isotope compositions of their shells. Our results show that clumped and oxygen isotope co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 66 publications
9
46
1
Order By: Relevance
“…This suggests that M. venosa present non-equilibrium growth-rate-related isotope effects up to about −2.9 ‰, larger than the approx. −1.5 ‰ previously recorded by Bajnai et al (2018). Provided that this offset can be constrained, brachiopods continue to present robust archives for palaeo-temperature reconstructions.…”
Section: Stable Isotope Variation Under Low-ph Conditionsmentioning
confidence: 85%
See 3 more Smart Citations
“…This suggests that M. venosa present non-equilibrium growth-rate-related isotope effects up to about −2.9 ‰, larger than the approx. −1.5 ‰ previously recorded by Bajnai et al (2018). Provided that this offset can be constrained, brachiopods continue to present robust archives for palaeo-temperature reconstructions.…”
Section: Stable Isotope Variation Under Low-ph Conditionsmentioning
confidence: 85%
“…It appears that there is about a 2 ‰ difference between the control specimen and samples from the acidification treatments (pH 7.35), with the last one being, strikingly, closer to the equilibrium with seawater DIC. Possibly, this illustrates the variability in kinetic effects (Bajnai et al, 2018), but may also be linked to changes in the source δ 13 C DIC in the control treatment. More studies are needed to fully answer this question.…”
Section: Stable Isotope Variation Under Low-ph Conditionsmentioning
confidence: 91%
See 2 more Smart Citations
“…The implication of having a different slope between Δ 47 value and temperature at 25 and 90°C means 10.1029/2019GC008209 Geochemistry, Geophysics, Geosystems that the acid fractionation correction would also vary with the fractionation factor decreasing as the absolute Δ 47 value of the carbonate becomes closer to a stochastic value. However, despite the observations of Wacker et al (2013) and the reanalysis of Defliese et al (2015), several workers have produced data that have shown there to be no dependence of the slope as a function of reaction temperature (Bajnai et al, 2018;Came et al, 2014;G. A. Henkes et al, 2013;Kelson et al, 2017).…”
Section: Phosphoric Acid Fractionation As a Function Of Reaction Tempmentioning
confidence: 99%